A cement emulsified asphalt mortar and its preparation method and application

By introducing anionic water-based polyurethane and cationic emulsified asphalt into cement emulsified asphalt mortar to form a spherical structure, the problems of poor compatibility with cement and asphalt and insufficient vibration reduction ability are solved, and the compressive strength and fatigue life of the material are improved. It is suitable for High-speed railway ball-free track.

CN116514489BActive Publication Date: 2024-12-24CHONGQING UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310497164.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-05
Publication Date
2024-12-24
Estimated Expiration
2043-05-05

AI Technical Summary

Technical Problem

The existing cement emulsified asphalt mortar has problems such as poor compatibility, insufficient vibration damping capacity, short fatigue life and large additive dosage in the ballastless tracks of high-speed railways, which is difficult to meet the high-performance needs of high-speed railways.

Method used

Anionic aqueous polyurethane and cationic emulsified asphalt are used to form a spherical structure, and the compatibility between cement and asphalt is improved through anionic and cationic interactions, and the compressive strength and rheological performance of the material are improved by optimizing the sand-ash ratio and stirring order.

Benefits of technology

It significantly improves the compressive strength, vibration damping ability and fatigue life of cement emulsified asphalt mortar, reduces the use of additives, improves the compatibility and construction performance of materials, and is suitable for plate ball-free tracks on high-speed railways and passenger dedicated lines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005124804300000061
    Figure GDA0005124804300000061
  • Figure GDA0005124804300000071
    Figure GDA0005124804300000071
  • Figure HDA0004212534590000011
    Figure HDA0004212534590000011
Patent Text Reader

Abstract

The present invention provides a novel cement emulsified asphalt mortar and a preparation method and application thereof, comprising the following components in parts by weight: 100 parts of cationic emulsified asphalt, 100 parts of cement and 150-200 parts of sand, and also comprising anionic waterborne polyurethane, wherein the addition amount of the anionic waterborne polyurethane is 0-20% of the mass of cement, and excluding 0. The present invention can better enable asphalt to exert its damping capacity through the selection of anions and cations, improve the compatibility of asphalt and cement, and reduce the contact of asphalt with external light, heat, rain and other aging factors, and effectively protect the asphalt that is easy to age. Therefore, the present invention greatly improves the rigidity and vibration reduction capacity of cement emulsified asphalt mortar under alternating loads, and significantly prolongs the fatigue life of CA mortar. The present invention is suitable for cement emulsified asphalt mortar for high-speed railways, passenger dedicated lines, and intercity railway slab ballastless tracks, and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of civil engineering material preparation, and specifically relates to a cement emulsified asphalt mortar and a preparation method and application thereof. Background Art

[0002] Cement emulsified asphalt mortar (CA mortar) is widely used in railway construction. It is one of the key structural layers of slab ballastless track. It is filled between the concrete base and the track plate. It is mainly composed of cement hydrate, demulsified asphalt and sand. It supports the prefabricated reinforced concrete track plate and provides the necessary strength and elasticity for the track. It is one of the core technologies of slab ballastless track. As a key material for high-speed railway ballastless track, CA mortar will have huge demand in the future. Therefore, it is of great significance to study its performance during construction and long-term use.

[0003] The cement in cement emulsified asphalt can react chemically with the water after the emulsified asphalt is demulsified, and the strength is formed quickly, which well balances the problem of emulsified asphalt demulsification and water repellency, and the type of cement has a great influence on the mechanical properties of emulsified asphalt concrete. For example, Fang et al. studied the mechanical properties of emulsified asphalt of different ion types and different types of cement (ordinary silicate, calcium sulfonate and calcium aluminate cement) after mixing and curing, and found that calcium sulfonate and calcium aluminate cement have a faster strength growth rate than ordinary silicate cement. Since traditional silicate cement forms strength slowly, it is difficult to meet the goal of rapid traffic. For example, the invention patent CN112723839A discloses a water-based environmentally friendly polyurethane modified emulsified asphalt cold mix, including the following components and the weight proportions of each component are: 11-12 parts of polyurethane modified room temperature composite emulsion; 100 parts of aggregate; 2 parts of high-strength mixed additives; 2 parts of water; 2-3 parts of water-based polyurethane, wherein the high-strength mixed additive is a mixture of special cement (sulfoaluminate cement), rubber powder and activator substances. Therefore, how to use ordinary silicate cement to quickly form the strength of CA mortar has become a hot topic in current research.

[0004] The emulsified asphalt used for cement emulsified asphalt mortar for high-speed railway and passenger dedicated line ballastless track is different from the emulsified asphalt used for highways. In addition to having conventional properties such as good storage stability and homogeneity, it should also have good compatibility with the strong alkaline cement mortar system, fluidity, vibration reduction ability and fatigue life. In recent years, researchers have learned from the experience of polymer-modified asphalt and polymer-modified cement, and tried to improve the workability, static mechanical properties, dynamic mechanical properties, durability and other properties of CA mortar through polymer modification. For example, the invention patent CN106904882B discloses a method for preparing emulsified asphalt cement mortar for slab ballastless track, which includes the following steps: first, a polyurethane / styrene butadiene latex core-shell structure with polyurethane as the shell and styrene butadiene latex as the core is prepared under the protection of a nitrogen atmosphere; a silane coupling agent is used to modify the base asphalt to obtain a silane coupling agent modified asphalt; a primary emulsifier, an auxiliary emulsifier, a polyurethane / styrene butadiene latex with a core-shell structure, a stabilizer, and a silane coupling agent modified asphalt are mixed evenly to obtain a modified emulsified asphalt; finally, cement, natural river sand, nano-silica sol, calcium sulfate whisker, air entraining agent, water reducer, expansion agent, setting regulator, defoamer, and water are mixed and stirred evenly, and then the modified emulsified asphalt prepared above is added, and the emulsified asphalt cement mortar for slab ballastless track is obtained after being stirred evenly. The invention patent CN103073235B discloses a cement emulsified asphalt mortar and a preparation method thereof. By weight, the cement emulsified asphalt mortar contains: 110-160 parts of emulsified asphalt, 10-30 parts of polymer emulsion, 90-100 parts of cement, 150-250 parts of sand, 0-0.5 parts of strength regulator, 0-10 parts of expansion agent, 0-1.0 parts of fiber, 0-0.05 parts of cellulose, 0.004-0.015 parts of aluminum powder, 0-0.1 parts of defoamer, 0-1.2 parts of air entraining agent, and 0-25 parts of water. By introducing the strength regulator, especially the compound use of the early strength agent and the retarder, the working performance, construction performance and long-term durability of the cement emulsified asphalt mortar under cold, warm and severe cold ambient temperatures can be effectively adjusted. Although the above-mentioned modified emulsified asphalt has improved its durability and low temperature resistance to a certain extent, its vibration reduction capacity and fatigue life are insufficient. At the same time, in practical applications, there are also disadvantages such as large additive dosage, environmental pollution, cement hydration and asphalt compatibility problems, resulting in easy segregation. And there is no relevant report on the effect of polyurethane ion type on cement emulsified asphalt modification. Summary of the invention

[0005] In view of the above problems existing in the prior art, the present invention provides a cement emulsified asphalt mortar and a preparation method and application thereof, which improves the compatibility between cement and asphalt, makes interface rupture less likely to occur, and solves the problems of insufficient vibration reduction ability, short fatigue life and large amount of additives in existing cement emulsified asphalt materials.

[0006] To achieve the above-mentioned purpose, the present invention adopts the following scheme: a cement emulsified asphalt mortar, comprising the following components in parts by weight: 100 parts of cationic emulsified asphalt, 100 parts of cement and 150-200 parts of sand, and also comprising anionic waterborne polyurethane, wherein the addition amount of the anionic waterborne polyurethane is 0-20% of the mass of cement, and excluding 0, the cationic emulsified asphalt is the core and the anionic waterborne polyurethane is the shell to form a spherical structure distributed in the cement matrix, and the compatibility between asphalt and cement is increased through the interaction between anions and cations.

[0007] Preferably, the cement is ordinary Portland cement.

[0008] Preferably, the asphalt content in the cationic emulsified asphalt is 50-60%; the polyurethane content in the anionic waterborne polyurethane is 35-50%.

[0009] Preferably, the mass ratio of sand to cement is 1.75. Thus, when the sand-to-cement ratio of CA mortar is 1.75, the compressive strength is the maximum. When the sand-to-cement ratio is greater than 1.75, the mortar separation remains substantially unchanged, but the compressive strength continues to decrease. Cement emulsified asphalt is a cementitious material. A suitable sand-to-cement ratio can give full play to the material properties. If there is too little sand, a "sand settling" phenomenon will occur, that is, the sand will sink to the bottom of the specimen, forming upper and lower layers with different densities. When there is too much sand, the cementitious material cannot fully bond the aggregate, resulting in a decrease in material strength.

[0010] Preferably, the anionic waterborne polyurethane is added in an amount of 5 to 10% of the mass of cement.

[0011] Another object of the present invention is to provide a method for preparing the above-mentioned cement emulsified asphalt mortar, comprising the following steps:

[0012] 1) adding anionic waterborne polyurethane to cationic emulsified asphalt and stirring at a low speed, then adding cement and sand and stirring at a high speed, and then stirring at a low speed to obtain a mixture;

[0013] 2) pouring the mixture prepared in step 1) into a mold for molding, demoulding after 1 day, and then placing the sample in a cement curing box for curing to obtain the cement emulsified asphalt mortar.

[0014] The study found that the mixing order is also very important. If polyurethane is mixed with cement first, the polyurethane will wrap the cement particles first, hindering the cement hydration reaction. If polyurethane is added after the mixing order, it will lead to uneven distribution of polyurethane. The compressive strength of the final prepared CA mortar will be significantly reduced.

[0015] Preferably, the speed of the low-speed stirring in step 1) is 100-200 rpm, the speed of the high-speed stirring is 300-500 rpm, and the stirring time is 30-120 seconds. The stirring time mainly affects whether the raw materials are mixed evenly, and the stirring rate affects the apparent density and gas content of the sample. Too high a speed may cause the gas content of the sample to be too high. In this way, the gas content of the product obtained under the conditions of the present invention is controlled between 10-12%.

[0016] Preferably, the curing in step 2) is performed by standing at a constant temperature and humidity of 20°C ± 3°C and 65% ± 5RH for 28 days.

[0017] Another object of the present invention is to provide an application of the above-mentioned cement emulsified asphalt mortar or the cement emulsified asphalt mortar prepared by the above-mentioned method in slab-type ballastless track.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. Anionic polyurethane is introduced into the cement emulsified asphalt mortar of the present invention, and anionic PU particles are adsorbed on the surface of asphalt particles to form a core-shell structure. As the cement is gradually hydrated, an inorganic-organic transition layer of PU-Al2O3-SiO2 is formed between asphalt and cement, which improves the compatibility problem between asphalt and cement. And this core-shell structure can better enable asphalt to exert its damping capacity, and also reduce the contact of asphalt with external light, heat, rain and other aging factors, and effectively protect the asphalt that is easy to age. Therefore, the present invention greatly improves the rigidity and vibration reduction capacity of cement emulsified asphalt mortar under alternating loads, and significantly prolongs the fatigue life of CA mortar. The present invention is suitable for cement emulsified asphalt mortar for high-speed railways, passenger dedicated lines, and intercity railway slab ballastless tracks, and is particularly suitable for cement emulsified asphalt mortar for high-speed railways, passenger dedicated lines, and intercity railway slab ballastless tracks in areas with highly intensive food chains, and has good application prospects.

[0020] 2. The present invention uses common silicate cement and anionic polyurethane, and further accelerates the early coagulation process of cement emulsified asphalt through anionic polyurethane, thereby improving its early strength. Moreover, anionic polyurethane can better improve the rheological properties and mechanical properties of CA mortar, and is more suitable for modified CA mortar. The present invention has a small amount of modifier and auxiliary agent added, low production cost, simple production process, easy industrialization, and is economical and practical. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Figure 2 is the mechanical properties of different cement emulsified asphalt mortars; A is the graph showing the variation of composite modulus with frequency, and B is the graph showing the variation of tanδ with frequency.

[0022] Figure 2The rheological curves of the cement emulsified asphalt mortars prepared in Comparative Examples 1 to 2 and Example 2 are shown.

[0023] Figure 3 Fatigue life of different cement emulsified asphalt mortars under different stress ratios and aging times; A is comparative example 1, and B is example 2.

[0024] Figure 4 The infrared spectra of cement emulsified asphalt mortar prepared from various raw materials and Example 2.

[0025] Figure 5 These are SEM images of cement emulsified asphalt mortar; a is comparative example 1, and b is example 2.

[0026] Figure 6 It is the spherical shell element analysis; A is the analysis area, and B is the EDS scanning result.

[0027] Figure 7 This is the SEM image of the structural distribution of anionic polyurethane in the cement matrix after asphalt etching. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with specific examples. The cement used in the following examples is ordinary Portland cement, and the sand is commercially available; the emulsified asphalt is produced using No. 70 asphalt as raw material and a cationic emulsifier, with a solid content of 50%; the anionic waterborne polyurethane (PU) has a solid content of 35%.

[0029] 1. A method for preparing cement emulsified asphalt mortar.

[0030] Example 1

[0031] A cement emulsified asphalt mortar comprises the following components in parts by weight: 100 parts of cationic emulsified asphalt, 100 parts of cement and 175 parts of sand, wherein the amount of anionic waterborne polyurethane added is 5% of the mass of cement; and is prepared by the following method:

[0032] (1) Anionic waterborne polyurethane was added to cationic emulsified asphalt and stirred at a low speed of 150 rpm for 120 s, cement and sand were then added and stirred at a high speed of 350 rpm for 90 s, and then stirred at a low speed of 150 rpm for 30 s to obtain a mixture.

[0033] (2) The mixture prepared in step 1) is poured into a mold for molding, and demolded after 1 day. The sample is then placed in a cement curing box for curing at a constant temperature and humidity of 20°C ± 3°C and 65% ± 5RH for 28 days to obtain the cement emulsified asphalt mortar.

[0034] Example 2

[0035] The addition amount of anionic waterborne polyurethane is 10% of cement, and the other steps are the same as in Example 1.

[0036] Example 3

[0037] The addition amount of anionic waterborne polyurethane is 15% of cement, and the other steps are the same as Example 1.

[0038] Example 4

[0039] The addition amount of anionic waterborne polyurethane is 20% of cement, and the other steps are the same as Example 1.

[0040] Comparative Example 1

[0041] No anionic waterborne polyurethane was added, and other steps were the same as in Example 2.

[0042] Comparative Example 2

[0043] The anionic waterborne polyurethane was replaced by the cationic waterborne polyurethane, and the other steps were the same as those in Example 2.

[0044] 2. Performance Testing

[0045] 1. The cement emulsified asphalt mortars prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were tested in the "Multi-Frequency-Strain" mode to determine the changes in the composite modulus and tanδ (loss factor) of the materials with increasing frequency. The frequency was applied in the range of 0-12 Hz, the temperature was maintained at 30°C, and the strain was 0.02%. The results are as follows: Figure 1 shown.

[0046] As can be seen from the figure, compared with Comparative Example 1, when the addition amount of anionic waterborne polyurethane is between 5 and 20wt.%, the loss factor increases with the increase of anionic waterborne polyurethane. When the addition amount of anionic waterborne polyurethane is 10wt.%, that is, Example 2, the composite modulus of cement emulsified asphalt mortar (CA mortar) reaches the best. When the addition amount of anionic waterborne polyurethane does not exceed 10wt.%, the composite modulus of CA mortar can be significantly improved, that is, under alternating loads, the stiffness of the material is also improved. Once the addition amount of anionic waterborne polyurethane exceeds 10wt.%, the composite modulus of CA mortar decreases with the addition of anionic waterborne polyurethane, which has a negative impact on the stiffness of CA mortar. It can be seen that the addition amount of anionic waterborne polyurethane of about 5-10wt.% can increase the composite modulus of CA mortar, and the loss factor is also improved, so that it has a good shock absorption effect. Compared with Comparative Example 2, the loss factor value of Example 2 is closer, but the composite modulus value of Example 2 is 7 to 8 times that of Comparative Example 2, which indicates that Example 2 has stronger rigidity than Comparative Example 2.

[0047] 2. According to the method of "Test Method for Water Consistency, Setting Time and Stability of Cement Standard Consistency" (GB1346-89), the initial setting time and final setting time of the mixtures prepared in Comparative Examples 1 to 2 and Example 2 were measured using a cement standard Vicat instrument (manufactured by Shanghai Luda). The results are shown in Table 1.

[0048] Table 1

[0049]

[0050] As can be seen from Table 1, the addition of cationic polyurethane will prolong the setting time of cement emulsified asphalt, while the addition of anionic polyurethane will shorten the setting time of cement emulsified asphalt. This indirectly proves that the addition of anionic polyurethane helps the cement to undergo hydration reaction in the system. In CA slurry, the main reactions are cement hydration and asphalt demulsification, among which cement hydration is the main source of strength. Therefore, anionic polyurethane can further improve the early strength of cement emulsified asphalt.

[0051] 3. The rheological properties of cement emulsified asphalt determine the difficulty of slurry injection and filling density during construction. The yield stress of the slurry reflects the minimum force required for the slurry to flow and deform. The smaller the yield stress of the slurry, the easier it is for the slurry to expand and flow. The rheological properties of the samples after mixing were tested using an AR1500ex dynamic shear rheometer (TA Instruments, USA). A parallel plate fixture with a diameter of 25 mm and a thickness of 1 mm was used. Since the rheological properties of the freshly mixed CA change over time due to cement hydration, the shear rate range of this experiment was 1-50 s. -1 , 10 points were taken, and a single experiment took 10 minutes to measure the changes in the yield stress and viscosity of each component CA with shear rate, simulating the influence of different mixing rates on the rheological properties of CA under actual construction conditions. The results are as follows Figure 2 shown.

[0052] From the experimental results, it can be seen that the rheological curve of CA shows a certain yield stress and shear thinning behavior. The Herschel-Bulkey model is used to fit the rheological curve, and Table 2 is obtained.

[0053] Table 2

[0054]

[0055] As can be seen from Table 2, the yield stress shows that the order is Comparative Example 2>Comparative Example 1>Example 2, and the plastic viscosity shows that the order is Comparative Example 1>Comparative Example 2>Example 2. The smaller yield stress is conducive to the expansion flow of CA mortar in the structure during construction, and the smaller plastic viscosity is conducive to the pumping of CA mortar in the pipeline during construction. The addition of anionic polyurethane reduces the yield stress and plastic viscosity of CA. Compared with the yield stress before modification, it is reduced by about 9.4%, and after the addition of cationic polyurethane, its plastic viscosity is also reduced compared with before modification, but the yield stress is increased by about 125% compared with before modification. After the addition of anionic polyurethane, the yield stress is greatly improved, and being closer to the value 1 indicates that the fluid properties are closer to Newtonian fluids, while the yield index of Comparative Example 2 and Comparative Example 1 does not change significantly. Therefore, compared with cationic PU, anionic PU is more capable of improving the rheological properties of CA.

[0056] In summary, compared with cationic polyurethane, anionic polyurethane can better improve the rheological and mechanical properties of CA mortar and is more suitable for modified CA mortar.

[0057] 4. CA materials are easily affected by the environment, such as ultraviolet radiation, humidity, etc. The xenon lamp aging box (SN-900, Nanjing Anai Testing Equipment) can simulate the full sunlight spectrum, control humidity, simulate rain, and reproduce the hazards that occur outdoors for months or even years in a few days or weeks. The samples prepared in Example 2 and Comparative Example 1 were fixed in the oven for 3d, 14d and 28d respectively, and the temperature was set to 38°C, the relative humidity was 70%, and the irradiation intensity was 60w / m 2 , the results are as follows Figure 3 shown.

[0058] As can be seen from the figure, the fatigue life of the samples prepared in Example 2 and Comparative Example 1 at the same stress ratio decreases with the increase of aging days. The addition of anionic PU not only improves the fatigue life of unaged CA, but also improves the fatigue life after aging more significantly compared with that before modification. The addition of anionic polyurethane especially enhances the anti-aging ability of the asphalt component.

[0059] 5. Fourier transform infrared spectrometer (IRAffinity-1S, Shimadzu) was used to characterize cement, emulsified asphalt, polyurethane and the product in Example 2 (CA-PU-10%). All samples were analyzed at 4000-700 cm -1 The test was conducted in the reflection mode within the range. Before the test, the emulsified asphalt and PU were fully heated to evaporate the water. Figure 4 shown.

[0060] It can be seen from the figure that the characteristic peak of the infrared spectrum of isocyanate dimer appears at 1750cm -1 ; Cement hydration products are between 4000-3500cm-1 The absorption peaks between 800 cm and 100 cm are consistent with those in CA-PU-10%, reflecting the Ca(OH)2 in cement hydrate and OH in crystal water. In addition, in the infrared spectrum of cement, the 800 cm absorption peak in calcium silicate hydrate (CSH) can also be seen. -1 Department Absorption peak caused by stretching vibration. At 1000-1100cm -1 There are two vibration peaks at 1015cm -1 and 1100cm -1 The absorption peaks at come from ettringite (AFt) and monosulfate (AFm) in the hydration products. From the infrared spectrum of CA-PU-10%, compared with the three raw materials, no new characteristic peaks are formed, and various peak types are retained and superimposed. This shows that cement, asphalt and polyurethane do not form new chemical groups during the mixing process.

[0061] 6. The samples of Example 2 and Comparative Example 1 were observed for micro / nano structure under a scanning electron microscope (JCM-7000, JEOL). The samples used for SEM observation were fracture interfaces caused by fatigue failure. The asphalt in the CA sample was fully dissolved after being soaked in toluene for 24 hours. By comparing the morphology before and after dissolving the asphalt, the distribution of asphalt and PU in the cement matrix can be obtained. The results are shown in Figure 2. Figure 5 shown.

[0062] As can be seen from the figure, in the sample of comparative example 1, the asphalt is distributed in the cement matrix in a film-like manner. This is because during the material preparation process, the reaction between cement and water in the emulsified asphalt causes the emulsified asphalt to lose its original solution environment, resulting in rapid demulsification. Therefore, as the cement hydration is gradually completed, the asphalt is distributed in the cement in a film-like manner. And in the cross section of CA, it can be clearly found that its fatigue section is broken along the asphalt-cement interface. One of the reasons for the relatively short fatigue life of CA is the poor compatibility between asphalt and cement. Due to the action of alternating loads, the direction in which the structure produces microcracks extends along the cement-asphalt interface. In the sample of Example 2, the asphalt is distributed in the cement in a spherical shape. This is because the full mixing of anionic PU and cationic emulsified asphalt will cause the PU particles to be adsorbed on the surface of the asphalt particles, forming a core-shell spherical structure distributed in the cement. Therefore, the asphalt particles present a regular spherical shape in the cement matrix. When the amount of anionic polyurethane added is less than 10%, since the amount of polyurethane is not enough to completely wrap all the asphalt, the distribution of the asphalt is film-like and spherical. When the anionic PU content is greater than or equal to 10%, the asphalt is distributed in the cement in a spherical form.

[0063] In order to determine the elemental composition of the spherical shell, first select points on the spherical shell for EDS point scanning. The scanning area and the results are as follows: Figure 6As shown. It can be seen from the figure that the main elements of the spherical shell are C, N, O, Al, Si (the main components of asphalt are C, O and S, etc., and the main components of cement are Ca, O, Al, Si, S, etc.). Since the sulfur content in the figure is weak, it can be inferred that the organic component is polyurethane. During the sample preparation process, anionic PU is adsorbed on the surface of cationic emulsified asphalt. With the gradual hydration of cement, an inorganic-organic transition layer of PU-Al2O3-SiO2 is formed between asphalt and cement, which improves the compatibility problem between asphalt and cement. In order to further confirm the structure formed by anionic PU on the asphalt surface, the sample was completely immersed in toluene to dissolve the asphalt, and then taken out to observe the morphology. The results are shown in Figure 7 As shown in the figure, after removing the asphalt, the originally full spherical structure is left with only a hollow shell, and the shell thickness is about 1μm. The comparison of the structure before and after etching shows that the PU phase is coated on the surface of the spherical asphalt phase, forming a core-shell structure, which effectively improves the compatibility between asphalt and cement, and can better enable the asphalt to exert its damping performance, reduce the contact of asphalt with external light, heat, rain and other aging factors, and effectively protect the asphalt that is prone to aging.

[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the applicant has described the present invention in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that modifications or equivalent substitutions of the technical solution of the present invention without departing from the purpose and scope of the technical solution of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A cement emulsified asphalt mortar, characterized in that: The invention comprises the following components in parts by weight: 100 parts of cationic emulsified asphalt, 100 parts of cement and 150-200 parts of sand, and also comprises anionic waterborne polyurethane, wherein the addition amount of the anionic waterborne polyurethane is 5-20% of the mass of the cement.

2. The cement emulsified asphalt mortar according to claim 1, characterized in that: The cement is ordinary Portland cement.

3. The cement emulsified asphalt mortar according to claim 1, characterized in that: The cationic emulsified asphalt has an asphalt content of 50-60%.

4. The cement emulsified asphalt mortar according to claim 1, characterized in that: The polyurethane content in the anionic waterborne polyurethane is 35-50%.

5. The cement emulsified asphalt mortar according to claim 1, characterized in that: The mass ratio of sand to cement is 1.

75.

6. The cement emulsified asphalt mortar according to claim 1, characterized in that: The addition amount of the anionic waterborne polyurethane is 5-10% of the mass of cement.

7. A method for preparing cement emulsified asphalt mortar according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1) Add anionic waterborne polyurethane to cationic emulsified asphalt and stir at a low speed, then add cement and sand and stir at a high speed, and then stir at a low speed to obtain a mixture; 2) pouring the mixture prepared in step 1) into a mold for molding, demoulding after 1 day, and then placing the sample in a cement curing box for curing to obtain the cement emulsified asphalt mortar.

8. The method for preparing cement emulsified asphalt mortar according to claim 7, characterized in that: In step 1), the speed of the low-speed stirring is 100-200 rpm, the speed of the high-speed stirring is 300-500 rpm, and the stirring time is 30-120 s.

9. The method for preparing cement emulsified asphalt mortar according to claim 7, characterized in that: The curing in step 2) is to stand for 28 days at a constant temperature and humidity of 20°C ± 3°C and 65% ± 5RH.

10. Use of the cement emulsified asphalt mortar according to any one of claims 1 to 6 or the cement emulsified asphalt mortar prepared by the method according to any one of claims 7 to 9 in slab-type ballastless track.